E-learning theory and practice - Haythornthwaite, Caroline A.; Andrews, Richard, 1953 Apr. 1- (Los Angeles : SAGE, 2011)
In'E-learning Theory and Practice', the authors set out different perspectives on e-learning. The book deals with the social implications of e-learning, its transformative effects, and the social and technical interplay that supports and directs e-learning.
Includes bibliographical references (p. [227]-254) and index.
Keywords: Internet in education; Computer-assisted instruction; Web-based instruction -- Social aspects; Internet -- Study and teaching